SWOT Analysis of the Economic Potential of Islamic Boarding Schools in Indonesia: NVivo Approach Study and Literature Review - Rohmadi, Rohmadi; Bagaskara, Doni Yusuf (LP2M IAIN Palopo, 2023)
This research aims to determine a SWOT analysis regarding the economic potential of Islamic boarding schools in Indonesia using the NVivo approach. This research uses qualitative methodology with the NVivo approach and literature review.